Molecular characterisation of a Theileria lestoquardi gene encoding a candidate sporozoite vaccine antigen - Skilton, Robert A.; Musoke, A.J.; Nene, Vishvanath M.; Wasawo, D.P.S.; Wells, C.W.; Spooner, P.R.; Bishop, Richard P.; Osaso, J.; Nkonge, C.; Latif, A.; Morzaria, S.P. (Elsevier, 2000)
Theileria are tick-transmitted, haemoprotozoan parasites infecting wild and domestic ungulates throughout many areas of the world. The most economically important species are T. parva and T. annulata which are pathogenic to cattle, and T. lestoquardi (syn hirci) which is pathogenic to sheep and goats. This report describes the cloning and analysis of the gene encoding the p67/SPAG-1 homologue of T. lestoquardi. This protein which is called SLAG-1 (sporozoite lestoquardi antigen 1), is predicted to have potential as a sporozoite - neutralisation antigen for inclusion in a sub-unit vaccine against T. lestoquardi infection of sheep and goats.